PENGARUH INFLASI DAN HARGA EMAS DUNIA TERHADAP IDX FINANCIALS DI BEI 2018-2022 - Markus, Morencia; Kaluge, David (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to analyze the influence of inflation and world gold prices on IDX Sector Financials during the period of 2018-2022 in Indonesia. Different patterns and varied impacts on stock prices during economic crises in Indonesia were found. Monthly secondary data in the form of time series for the period of 2018-2022 were used in this study. The data analysis method employed was the Autoregressive Distributed Lag (ARDL) model. The research findings indicate that in the short term, inflation has a negative and significant effect on IDX Sector Financials, while world gold prices have a positive and significant influence. In the long term, inflation does not have an impact on IDX Sector Financials, and world gold prices also have a positive and significant effect. However, this study has limitations, and further research is recommended to expand the observation period and consider additional independent variables and other relevant factors related to IDX Sector Financials. This would provide clearer results and allow for broader generalization within a more extensive scope.